2021
DOI: 10.3390/ijms22189660
|View full text |Cite
|
Sign up to set email alerts
|

14,15-EET Reduced Brain Injury from Cerebral Ischemia and Reperfusion via Suppressing Neuronal Parthanatos

Abstract: To investigate the effect of 14,15-EET on the parthanatos in neurons induced by cerebral ischemia and reperfusion, middle cerebral artery occlusion and reperfusion (MCAO/R) and oxygen glucose deprivation/reoxygenation (OGD/R) were used to simulate cerebral ischemia reperfusion in vivo and in vitro, respectively. TTC staining and the Tunel method were used to detect cerebral infarct volume and neuronal apoptosis. Western blot and immunofluorescence were used to detect poly (ADP-ribose) polymerase-1 (PARP-1) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…14, 15‐EET is an important intermediate in the process of arachidonic acid metabolism in organisms and has various cytoprotective effects. Our previous study has found that 14, 15‐EET can reduce cerebral ischemia–reperfusion‐induced neuronal apoptosis by promoting mitochondrial biogenesis and inhibiting the mitochondrial apoptosis pathway and parthanatos in neurons 26–28 . This study shows that 14, 15‐EET can reduce neuronal apoptosis and cerebral infarct volume, and alleviate neurological impairment following MCAO, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…14, 15‐EET is an important intermediate in the process of arachidonic acid metabolism in organisms and has various cytoprotective effects. Our previous study has found that 14, 15‐EET can reduce cerebral ischemia–reperfusion‐induced neuronal apoptosis by promoting mitochondrial biogenesis and inhibiting the mitochondrial apoptosis pathway and parthanatos in neurons 26–28 . This study shows that 14, 15‐EET can reduce neuronal apoptosis and cerebral infarct volume, and alleviate neurological impairment following MCAO, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study has found that 14, 15-EET can reduce cerebral ischemia-reperfusion-induced neuronal apoptosis by promoting mitochondrial biogenesis and inhibiting the mitochondrial apoptosis pathway and parthanatos in neurons. [26][27][28] This study shows that 14, 15-EET can reduce neuronal apoptosis and…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The levels of ROS indicators such as MDA, SOD, and nitric oxide (NO) in rat neurons were detected, and XBJ injection was demonstrated to partially offset the HS-induced elevation in the MDA and NO levels, while upregulated SOD levels in rat neurons (Figure E; p < 0.05, p < 0.01 and p < 0.001). Neuron cell death occurs during pathology, and our previous work has revealed that the death rate of neuron cells after HS is approximately 25–30%, which indicates other potential mechanisms of cell death besides apoptosis and autophagy. ROS is reported to induce PARP-1-dependent cell death, also named Parthanatos, which is potentially involved in HS-induced brain injury. , We, therefore, detected the involvement of PARP-1 in HS-induced neuron cells. Our results demonstrated that HS induced an increase in PARP-1 mRNA and protein levels, which was counteracted by the treatment of XBJ injection, suggesting that XBJ injection mitigates the HS-induced Parthanatos of neurons by inhibiting the activation of PARP-1 (Figure F,G; p < 0.001).…”
Section: Resultsmentioning
confidence: 84%
“…29−31 ROS is reported to induce PARP-1-dependent cell death, also named Parthanatos, which is potentially involved in HS-induced brain injury. 32,33 We, therefore, detected the involvement of PARP-1 in HS-induced neuron cells. Our results demonstrated that HS induced an increase in PARP-1 mRNA and protein levels, which was counteracted by the treatment of XBJ injection, suggesting that XBJ injection mitigates the HS-induced Parthanatos of neurons by inhibiting the activation of PARP-1 (Figure 2F,G; p < 0.001).…”
Section: ■ Resultsmentioning
confidence: 97%